Analisis Pemahaman dan Kepatuhan terhadap Prinsip Syariah dalam Proses Klaim Asuransi Syariah - Riri Dwita Putri; Zainarti Zainarti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze participants’ understanding and compliance with sharia principles in the sharia insurance claim process in Indonesia. Sharia insurance, which is based on the principle of mutual assistance and tabarru’ contract, is expected to provide protection in accordance with Islamic law. However, challenges arise in its operational practices, especially in the claim process. This study uses a qualitative approach by interviewing sharia insurance participants to explore their level of understanding of sharia principles, claim procedures, and challenges faced during the claim process. The results of the study indicate that participants’ understanding of sharia principles is still limited, which has an impact on their lack of clarity in undergoing the claim procedure. Some of the main challenges identified include administrative constraints, long claim processing times, and unclear claim procedures. Lack of understanding of sharia principles also worsens the smoothness of claims. Based on these findings, this study suggests the importance of increasing sharia literacy through training, seminars, and educational materials that are easy for participants to understand. In addition, simplification of claim procedures is needed to increase transparency and ensure that the claim process is in accordance with sharia principles. The implication of this study is the importance of improvements in the education system and operations of sharia insurance to improve participant understanding and compliance, as well as strengthen trust in the sharia insurance industry in Indonesia.